A simplicial analysis of the fMRI data from human brain dynamics under functional cognitive tasks - Bishal, Rabindev; Cherodath, Sarika; Singh, Nandini Chatterjee; Gupte, Neelima (Frontiers in Network Physiology, 2022)
The topological analysis of fMRI time series data has recently been used to characterise the identification of patterns of brain activity seen during specific tasks carried out under experimentally controlled conditions. This study uses the methods of algebraic topology to characterise time series networks constructed from FMRI data measured for adult and children populations carrying out differentiated reading tasks. Our pilot study shows that our methods turn out to capable of identifying distinct differences between the activity of adult and children populations carrying out identical reading tasks. We also see differences between activity patterns seen when subjects recognise word and nonword patterns. The results generalise across different populations, different languages and different active and inactive brain regions.